Strategies to Attract Private Transport to Public Transport - Damayanti, Yulinar Rizky; Sebayang, Lesta Karolina Br (Efficient: Indonesian Journal of Development Economics, 2019)
The purpose of this research is to develop appropriate policy strategies to attract users to switch modes from private transport to public transport. This research is quantitative research. This research uses the Analysis Hierarchy Process (AHP). The number of interviewees in this study as many as 8 keyperson. Research results indicate that transportation is the most criteria priority has a value weight of 0.612, then the user's criteria of 0.251 became the second prioritized criteria, and the last is the policy criteria the Government of 0.137. Based on the results of the research of the advice given by researchers, namely; the rejuvenation of old age transportation, provide coaching to driver-driver BRT, adding to the shelter-shelter at points of housing and shopping, as well as add new routes in order to reach out to suburban areas. Tujuan dari penelitian ini adalah untuk mengembangkan strategi kebijakan yang tepat untuk menarik pengguna untuk beralih moda dari angkutan pribadi ke angkutan umum. Penelitian ini adalah penelitian kuantitatif. Penelitian ini menggunakan Analisis Hierarki Proses (AHP). Jumlah yang diwawancarai dalam penelitian ini sebanyak 8 keyperson. Hasil penelitian menunjukkan bahwa transportasi adalah prioritas kriteria terbanyak yang memiliki bobot nilai 0,612, maka kriteria pengguna 0,251 menjadi kriteria prioritas kedua, dan yang terakhir adalah kriteria kebijakan Pemerintah 0,137. Berdasarkan hasil penelitian atas saran yang diberikan oleh peneliti, yaitu; peremajaan transportasi usia tua, memberikan pembinaan kepada pengemudi-pengemudi BRT, menambah shelter-shelter di titik-titik perumahan dan perbelanjaan, serta menambah rute baru guna menjangkau wilayah pinggiran kota